Morphological alterations in the congenital blind based on the analysis of cortical thickness and surface area - Park, Hae-Jeong; Lee, Jong Doo; Kim, Eung Yeop; Park, Bumhee; Oh, Maeng-Keun; Lee, SungChul; Kim, Jae-Jin (NeuroImage (Orlando, Fla.), 2009)
To explore the morphological aspects of the functional reorganization of the blind's visual cortex, we analyzed the regional cortical thickness and cortical surface area in the congenitally blind subjects (CB) compared to the late-onset blind (LB) and sighted controls (SC). Cortical thickness was calculated from high-resolution T1-weighted magnetic resonance images of 21 young CB (blind from birth, mean age=27.1 yr), 12 LB, and 35 young SC. Analysis of covariance of cortical layer thickness with global thickness, age, and gender as covariates was done node-by-node on the entire cortical surface. Further analysis of mean thickness and surface area was performed for 33 automatically parceled cortical regions. Voxel-based morphometry was also conducted to compare results with cortical thickness and surface area. We found increased cortical thickness in the regions involved in vision and eye movement, such as the pericalcarine sulcus, cingulate cortex, and right frontal eye field, but cortical thinning in the left somatosensory cortex and right auditory cortex of CB compared to SC. CB had significantly reduced surface extent in the primary and associated visual areas, which explains volumetric atrophies in the visual cortex of CB despite increased cortical thickness. Conversely, LB tended to have cortical thinning in the primary visual cortex with a slight or no significant reduction in the surface extent. These morphological alterations in CB may indicate cortical reorganization at the visual cortex in connection with other sensory cortices.